This discussion board is a place to discuss our Daily Challenges and the math and science
related to those challenges. Explanations are more than just a solution — they should
explain the steps and thinking strategies that you used to obtain the solution. Comments
should further the discussion of math and science.

When posting on Brilliant:

Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .

Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.

Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.

Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

Markdown

Appears as

*italics* or _italics_

italics

**bold** or __bold__

bold

- bulleted - list

bulleted

list

1. numbered 2. list

numbered

list

Note: you must add a full line of space before and after lists for them to show up correctly

Now, the claim $\sqrt[n]{n!} \ge \sqrt{n}$ is equivalent to $(n!)^2 \ge n^n$. We will prove this by induction. The base cases are $n = 1, 2, 3$ in which it is true. Now suppose that it's true for some $n \ge 3$, and we'll prove the claim for $n \gets n+1$.

We have to prove $(n!)^2 \ge n^n$. Instead of proving it using Sterling's approximation or induction here is a solution on AM-GM. I found a nice form of $(n!)^2$ recently. $(n!)^2=[1 \cdot n][2 \cdot (n-1)]\ldots[n \cdot1]$(there are $n$ terms). Now, for some variable $m$, such that $1 \le m \le n$ we have $m(n-m+1) \ge n$. The result follows.

Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in`\(`

...`\)`

or`\[`

...`\]`

to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestSo I will give an inductive, calculus-requiring proof.

Lemma 1: $\left( 1 + \frac{1}{n} \right)^n \le e$ for all positive integer $n$.One way to prove it is to observe that $1 + \frac{1}{n} \le 1 + \frac{2}{2n} + \frac{1}{4n^2} = \left( 1 + \frac{1}{2n} \right)^2$, thus by induction,

$\displaystyle\begin{aligned} \left(1 + \frac{1}{n} \right)^n &\le \left(1 + \frac{1}{2n} \right)^{2n} \\ &\le \left(1 + \frac{1}{4n} \right)^{4n} \\ &\le \ldots \\ &\le \lim_{k \to \infty} \left(1 + \frac{1}{2^k n} \right)^{2^k n} \\ &= \lim_{n \to \infty} \left(1 + \frac{1}{n} \right)^n \\ &= e \end{aligned}$

Lemma 2: $e < 3$$\displaystyle\begin{aligned} e &= \frac{1}{0!} + \frac{1}{1!} + \frac{1}{2!} + \frac{1}{3!} + \frac{1}{4!} + \frac{1}{5!} + \frac{1}{6!} + \ldots \\ &< 1 + \frac{1}{1} + \frac{1}{2} + \frac{1}{4} + \frac{1}{8} + \frac{1}{16} + \frac{1}{32} + \ldots \\ &= 1 + 2 \\ &= 3 \end{aligned}$

Now, the claim $\sqrt[n]{n!} \ge \sqrt{n}$ is equivalent to $(n!)^2 \ge n^n$. We will prove this by induction. The base cases are $n = 1, 2, 3$ in which it is true. Now suppose that it's true for some $n \ge 3$, and we'll prove the claim for $n \gets n+1$.

$\displaystyle\begin{aligned} ((n+1)!)^2 &= (n!)^2 \cdot (n+1)^2 \\ &\ge n^n \cdot (n+1)^2 \\ &\ge n^n \cdot (n+1) \cdot e & \text{by Lemma 2, because \$n \ge 3 > e\$} \\ &\ge n^n \cdot (n+1) \cdot \left( 1 + \frac{1}{n} \right)^n & \text{by Lemma 1} \\ &= \left(n + \frac{n}{n} \right)^n \cdot (n+1) \\ &= (n+1)^n \cdot (n+1) \\ &= (n+1)^{n+1} \end{aligned}$

Log in to reply

We have to prove $(n!)^2 \ge n^n$. Instead of proving it using Sterling's approximation or induction here is a solution on AM-GM. I found a nice form of $(n!)^2$ recently. $(n!)^2=[1 \cdot n][2 \cdot (n-1)]\ldots[n \cdot1]$(there are $n$ terms). Now, for some variable $m$, such that $1 \le m \le n$ we have $m(n-m+1) \ge n$. The result follows.

Log in to reply

Wise solution!

Log in to reply

Nice solution

Log in to reply

Why is it that for a variable $m$

$1\leq m\leq n$ is $m(n-m+1)\geq n$ ?

Log in to reply

Take $n=m+k$ where $k \ge 0$. The inequality simplifies to $m(k+1) \ge m+k$ or $mk+m \ge m+k$ or $m \ge 1$ which is true.

Log in to reply

Log in to reply

$\sqrt[n]{n!} \geq \sqrt{n}$

${n!} \geq {\sqrt{n}}^n$

$(n) \cdot (n-1) \cdot (n-2) \cdot \dots \cdot (1) \geq {\sqrt{n}}^n$

$(n)(1) \cdot (n-1)(1+1) \cdot (n-2)(1+2) \cdot \dots \cdot (\frac{n+1}{2})(\frac{n-1}{2}) \geq {\sqrt{n}}^n$ or $(n)(1) \cdot (n-1)(1+1) \cdot (n-2)(1+2) \cdot \dots \cdot (\frac{n}{2}) \geq {\sqrt{n}}^n$

We note that (n-k)(1+k) > n for all -1<k<n+1. So the result follows. By the way, i was sniped by Svatejas Shivakumar.

Log in to reply

Ninja'ed haha tfs

Log in to reply

Well what about n-1?

Log in to reply